2021
DOI: 10.2147/aabc.s290912
|View full text |Cite
|
Sign up to set email alerts
|

In silico Molecular Docking, DFT Analysis and ADMET Studies of Carbazole Alkaloid and Coumarins from Roots of Clausena anisata: A Potent Inhibitor for Quorum Sensing

Abstract: Introduction In modern drug design, in silico methods are largely used to understand drug-receptor interactions and quantum chemical properties. In the present study, a computational de novo design approach was used to confirm mode of binding for antibacterial activity, elucidating quantum chemical properties and ADMET-drug-likeness of carbazole alkaloid ( 1 ) and three coumarins ( 2 – 4 ) isolated from roots of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…The higher HOMO value states that molecule with a good electron donor, whereas a lower value indicates a weak electron acceptor. Moreover, a smaller energy gap between the LUMO and HOMO energies has a considerable influence on the intermolecular charge transfer and bioactivity of molecules [23]. In the current study the tangeretin and its derivatives L8 and L13 were found to possess less energy gap which supports their ability to binding with receptors.…”
Section: Fig 2 Binding Interactions (2d) Of Ligands With Leptin -1ax8supporting
confidence: 54%
“…The higher HOMO value states that molecule with a good electron donor, whereas a lower value indicates a weak electron acceptor. Moreover, a smaller energy gap between the LUMO and HOMO energies has a considerable influence on the intermolecular charge transfer and bioactivity of molecules [23]. In the current study the tangeretin and its derivatives L8 and L13 were found to possess less energy gap which supports their ability to binding with receptors.…”
Section: Fig 2 Binding Interactions (2d) Of Ligands With Leptin -1ax8supporting
confidence: 54%
“…Additionally, gastrointestinal (GI) and blood–brain barrier (BBB) permeation indicate the absorption and distribution of drug molecules. 34 , 35 The in-silico prediction results of absorption, distribution, metabolism and excretion (ADME) of the compounds ( 1 , 3 – 5 ) studied are presented in ( Table 5 ). The Swiss ADME prediction parameters indicated that N-methyl-2,3-bis(2-hydroxybenzyl)-1Н-indol ( 1 ) and coumarin ( 5 ) showed high gastrointestinal (GI) absorption, whereas ( 3 and 4 ) displayed low absorption.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking studies of the synthesized compounds ( 7 – 11 ) against target proteins (human peroxiredoxin 5 PDB ID: 1HD2 and E. coli DNA gyrase B PDB ID: 6F86) were performed using AutoDock Vina 4.2 (MGL tools 1.5.7) following standard protocol [ 55 , 56 ]. The three- and two-dimensional construction of the compounds, energy minimization of the synthesized compounds, docking simulations, crystal structures of the receptor molecules ( E. coli DNA gyrase B, PDB ID: 6F86 [ 57 ]; and human peroxiredoxin 5, PDB ID: 1HD2 [ 58 ], protein preparation, docking algorithm and ligand representations were conducted following the same procedure and protocols reported in our previous work [ 59 , 60 ].…”
Section: Methodsmentioning
confidence: 99%